Exploring Context-Rich Problems for Complex Problem-Solving in Electricity Courses: Comparative Perspectives from Indonesian Universities - Sohibun; Setiawan, Agus; Samsudin, Achmad; Suhandi, Andi; Kapıcı, Hasan Özgür; Budiman, Deni Moh; Zulva, Rahmi (Universitas Islam Negeri Raden Intan Lampung, 2026)
Higher education today requires pedagogies that not only teach technical skills but also transform the ways students think and engage with knowledge. This study investigates the use of context-rich problems (CRPs) as a framework for developing complex problem-solving (CPS) in university-level electricity courses. Using a qualitative case study design, data were collected from 34 students across four Indonesian universities, representing diverse cultural and institutional settings. The findings show that CRPs encouraged transformative learning by shifting students from procedural problem-solving to reflective, expert-like practices, such as qualitative reasoning, iterative planning, and selective information seeking. Contextual differences emerged: students in stronger academic environments demonstrated greater confidence and ability to connect theory with authentic contexts, while others relied more on formulaic strategies. These results highlight the influence of sociocultural and institutional contexts on transformative engagement. Embedding CRPs in science education can therefore foster conceptual understanding, critical awareness, and agency in approaching complex real-world problems. Furthermore, the study suggests that educators should consider incorporating CRPs into curricula to facilitate deeper learning experiences, particularly in fostering the skills necessary to tackle modern, interdisciplinary challenges.